Potensi gel Stichopus hermanii dan Hyperbaric Oxygen Therapy untuk mempercepat perawatan ortodontiPotential of Stichopus hermanii gel and Hyperbaric Oxygen Therapy in accelerating orthodontic treatment - I Ketut Ika Sandana; Jessica Velisia; Alexander Yunior; Arya Brahmanta; Noengki Prameswari (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2017)
Pendahuluan: Perawatan ortodonti memerlukan inovasi untuk mempercepat waktu perawatan. Perawatan ortodonti menyebabkan adanya daerah tekanan dan tarikan yang dipengaruhi oleh ekspresi Receptor Activator of Nuclear Factor Kappa-b (RANK) pada daerah tekanan, yang merangsang osteoklas dan ekspresi osteoprotegerin pada daerah tarikan yang merangsang osteoblast. Stichopus hermanii mempunyai efek pada proses penyembuhan, Hyperbaric Oxygen Therapy (HBOT) memberikan efek remodelling. Studi pustaka ini bertujuan untuk mengungkapkan mekanisme potensi gel Stichopus hermanii dan Hyperbaric Oxygen Therapy (HBOT) dalam mempercepat proses pergerakan gigi pada perawatan ortodonti sebagai alternatif terapi. Studi Pustaka: Inovasi untuk mempercepat perawatan ortodonti dilakukan pada daerah tekanan dan tarikan. Pemberian gel Stichopus hermanii secara lokal dapat meningkatkan level osteoprotegerin yang menghambat ikatan antara Receptor Activator of Nuclear Factor Kappa-b Ligand (RANK-L) dan Receptor Activator of Nuclear Factor Kappa-b (RANK), sehingga menghambat aktivasi osteoklas dan mengaktivasi aposisi tulang. Hyperbaric Oxygen Therapy menstimulasi ekspresi RANK pada daerah tekanan membantu mempercepat proses resorpsi. Kombinasi gel Stichopus hermanii dan Hyperbaric Oxygen Therapy menyebabkan pergerakan gigi meningkat melalui proses remodelling. Simpulan: Inovasi kombinasi terapi gel Stichopus hermanii dan Hyperbaric Oxygen Therapy dapat meningkatkan pergerakan gigi pada perawatan ortodonti.Kata kunci: Pergerakan gigi ortodonti, Stichopus hermanii, Hyperbaric Oxygen Therapy, osteoprotegerin, RANK-L, RANK.  ABSTRACTIntroduction: Orthodontic treatment requires innovation to accelerate the treatment time — orthodontic treatment is resulting in pressure and pull area that is affected by the expression of the Receptor Activator of Nuclear Factor Kappa b (RANK) in the pressure region, which stimulates osteoclasts and expression of osteoprotegerin in the pulling region which stimulates the osteoblast. Stichopus hermanii affects the healing process, Hyperbaric Oxygen Therapy (HBOT) provides a remodelling effect. This literature study was aimed to reveal the potential mechanism of Stichopus hermanii and Hyperbaric Oxygen Therapy (HBOT) in accelerating the tooth movement process in orthodontic treatment as an alternative therapy. Literature Review: Innovations to accelerate orthodontic treatment were performed in the pressure and pull area. Administration of Stichopus hermanii gel could increase the level of osteoprotegerin which inhibits the bond between Receptor Activator of Nuclear Factor Kappa-b Ligand (RANK-L) and Receptor Activator of Nuclear Factor Kappa-b (RANK), thus inhibiting osteoclast activation and activating bone apposition. Hyperbaric Oxygen Therapy (HBOT) stimulates RANK expression in the pressure area to help accelerate the resorption process. Combinations of Stichopus hermanii gel and HBOT cause tooth movement to increase through the remodelling process. Conclusion: An innovative combination of Stichopus hermanii gel and Hyperbaric Oxygen Therapy (HBOT) was able to improve the tooth movement in orthodontic treatment.Keywords: Orthodontic tooth movement, Stichopus hermanii gel, Hyperbaric Oxygen Therapy, osteoprotegerin, RANK-L, RANK.